Efektivitas Teori Konseling Perilaku dengan Teknik Self Management dalam Meningkatkan Prestasi Pribadi dan Ketahanan Diri pada Siswa Kelas VII MTS Mardlatillah Singaraja - Dharsana, I Ketut; Umam, Ahmad Khotibul (Jurnal IKA, 2024)
Personal achievement is a very important personality element to encourage students to have a need for achievement in facing challenges. Meanwhile, personal defence is the need to take a yielding and tolerant position to maintain balance. The aims of this research are: (1) to test the effectiveness of Behavioral counseling theory, self-management techniques in increasing personal achievement at MTs Mardlatillah Singaraja and (2) to test the effectiveness of Behavioral counseling theory, self-management techniques in increasing personal defence at MTs Mardlatillah Singaraja. This research design uses a one group pretest-posttest design. The research population was all class VII students at Mts Mardlatillah, totaling 90 students. The research sample was taken using random sampling and random class techniques as an intact group. Therefore, based on the lottery results, classes VII A and VII C were obtained as research samples. Statistical tests use the t-test to determine the effectiveness of the treatment that has been carried out. H0 is rejected if tcount > ttable. H0 is accepted if tcount ≤ ttable. The H1 hypothesis test which was carried out based on the t-test obtained tcount of 1.851 while ttable with db N-1 = 30 – 1 = 29 and a significance level of 5% (0.05) was 1.699. Meanwhile, for the H2 hypothesis test which was carried out based on the t-test, the tcount was 1.880, while the ttable with db N-1 = 30 – 1 = 29 and a significance level of 5% (0.05) was 1.699. Because tcount > ttable it can be concluded that H0 is rejected, H1 and H2 are accepted.